Format Sistem Bagi Hasil dalam Pengelolaan Hutan Bersama Masyarakat dengan Sistem Agroforestri - Noorvitastri, Hanny; Wijayanto, Nurheni (Jurnal Manajemen Hutan Tropika, 2003)
The purposes of this research are to know the feasibility of the sharing form, to find the sharing form which can improve of forest quality and local society welfare, and to identify factors which influence the sharing form implemented by PT.Perhutani and local society. This research was carried out in Cileuya village, Cimahi subdirect, Kuningan regency. The sharing form implemented by PT.Perhutani and local society who lives surrounding the forest was 20percent : 80percent. The mechanism of the sharing was for the primary plants that is super teak. PT. Perhutani get 80percent, while the society get 20percent For bananas, petai and mango tree, PT. Perhutani get 20percent while the society get 80percent. To know the feasibility the sharing form, the study then used NPV, BCR and lRR project indicators. Among all of the sharing form examined, the study found that the sharing form of 25percent : 75percent was the most feasible one to be used than others.